2013
DOI: 10.1371/journal.pone.0060491
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Balance Disorders during a Daily Living Movement in Obese: Can Biomechanical Factors Explain Everything?

Abstract: Obese people suffer from postural deficits and are more subject to falls than their lean counterpart. To improve prevention and post-fall rehabilitation programs, it seems important to better understand the posturo-kinetic disorders in daily life situations by determining the contribution of some key factors, mainly morphological characteristics and physical activity level, in the apparition of these disorders.Twelve severe android obese and eight healthy non obese adults performed a reaching task mobilizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 51 publications
2
30
0
7
Order By: Relevance
“…Observaram que indivíduos com IMC acima de 30 Kg/m² apresentaram redução no tempo de manutenção quando comparados com não obesos 12,13 . Outros estudos demonstraram atraso de 20 a 40% do impulso motor e sensorial sobre o nervo mediano, ulnar, fibular e tibial, quando comparado com sujeitos não obesos sugerindo redução do recrutamento de unidades motoras e da força muscular 14 . Pesquisas referem à influência do IMC no equilíbrio postural estático e dinâmico em indivíduos idosos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Observaram que indivíduos com IMC acima de 30 Kg/m² apresentaram redução no tempo de manutenção quando comparados com não obesos 12,13 . Outros estudos demonstraram atraso de 20 a 40% do impulso motor e sensorial sobre o nervo mediano, ulnar, fibular e tibial, quando comparado com sujeitos não obesos sugerindo redução do recrutamento de unidades motoras e da força muscular 14 . Pesquisas referem à influência do IMC no equilíbrio postural estático e dinâmico em indivíduos idosos.…”
Section: Discussionunclassified
“…Por meio do mecanismo sensorial, os mecanorreceptores ativos durante a absorção do impacto dos pés no solo influenciam nos segmentos adjacentes 21 . As alterações posturais acontecem em conjunto, por exemplo, quando um pé pronado toca o solo, provavelmente será observada rotação interna da tíbia, joelho valgo, rotação medial do fêmur e queda da pelve contralateral 14 . Essas alterações podem ter origem ascendente ou descendente, levando a adequação postural de toda a cadeia cinética do membro inferior.…”
Section: Discussionunclassified
“…There is also a large body of evidence suggesting that obese patients have displaced centers of mass and altered gait kinematics and are at increased risk of falls. 15,16 In a morbidly obese patient with a generous soft tissue envelope, deformity of the femur and tibia at the knee can be difficult to assess clinically. This can result in dulled suspicion at the time of index evaluation and a delay to radiography.…”
mentioning
confidence: 99%
“…A recent study found that movement speed during a motor control behavior task is slower in inactive obese individuals compared with active ones (Mignardot, Olivier, Promayon, & Nougier, 2013). The fact that overweight participants were physically active in our study might have enhanced their muscle function and strength, and consequently their response strength, enabling them to maintain a similar latency response to unexpected external perturbation.…”
Section: Resultsmentioning
confidence: 59%